Republic of Croatia : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that after six years of persistent recession, Croatia's economy is showing first signs of recovery. Robust retail sales and value-added tax receipts suggest that private consumption has bottomed out. Employment has stabilized and corporate profits are recovering. Tailwinds from a favorable external environment have helped, notably lower energy prices, stronger euro area growth, and ample domestic and external liquidity that contain debt servicing costs. For 2015, the economy is projected to grow by 0.5 percent. Net exports are expected to make a modest positive contribution to growth.